By-Laws, Rules and Regulations : 2003. (By Laws, Rules and Regulations; Fifty Ninth Issue, May 2003, 2003)
This paper discusses the 59th issue of the By-Laws and Rules and Regulations of the IMF. The By-Laws are adopted under the authority of, and are intended to be complementary to, the Articles of Agreement of the IMF. The Rules and Regulations supplement the Articles of Agreement and the By-Laws adopted by the Board of Governors. They are not intended to replace any provision of either the Articles or the By-Laws. The Rules and Regulations provide such operating rules, procedures, regulations, and interpretation as are necessary and desirable to carry out the purposes and powers contained in the Articles, as supplemented by the By-Laws.